Virus and virus-like diseases of citrus in Greece and certification - Kyriakopoulou P.E. (Proceedings of the Mediterranean network on certification of citrus. 1995-1997, 1998)
Most of the citrus virus diseases are present in Greece: impietratura, concave gum, psorosis complex, blind pocket, cristacortis, crinkly leaf, infectious variegation, exocortis, cachexia, gummy bark and woody gall. Quarantine measures are applied against the introduction of tristeza and stubborn. Legislative measures and institutions involved in the production of healthy propagating material are described. Certified material is indexed in glasshouse and in the field for tristeza, tristeza seedling yellows, vein enation-woody gall, exocortis, cachexia, stubborn, infectious variegation, psorosis complex, concave gum, impietratura, cristacortis.
Round Table on: Citrus Virus and Virus-like Diseases and Certification: State of the Art, 1995/07/21, Bari (Italy)